Sistem Pendukung Keputusan Menentukan Sales Terbaik Menerapkan Metode Simple Additive Weighting (SAW) - Rima Tamara Aldisa; Fifto Nugroho; Mesran Mesran; Susi Agustini Sinaga; Kelik Sussolaikah (Journal of Information System Research (JOSH), 2022)
In this study, the author uses the SAW (Simple Additive Weighting) method to determine the best sales at marketing company. The SAW method is considered appropriate in determining the best sales because the SAW method performs the weighted summation process of the performance rating on each alternative on all attributes. This research was conducted by determining the criteria, alternatives and weights, then carried out the matrix preparation process, calculating normalization and calculating preferences. So from the results of the calculation of preferences, a ranking process is carried out to determine the best alternative. The results of the study provide recommendations for the 6th alternative which has the highest value with a value of 0.879 being the best sales.